Fibrinogen and colorectal cancer: A study of the Chinese population - Jinfeng Wang; Jingjing Li; Jing Huo; Yaxi Zhao; Kangkang Liu; Huijie Wang; Xu Cao (PLoS ONE, 2025)
Fibrinogen has been associated with a variety of malignancies, including colorectal cancer (CRC). However, there is no study on the relationship between fibrinogen and CRC specifically in the Chinese population. The objective of this study was to analyze the relationship between fibrinogen and CRC in the Chinese population. This study included consecutive inpatients undergoing colonoscopies (April 2015‒June 2022). A total of 3,595 individuals, comprising 468 CRCs and 3,127 controls, were included. Logistic regression models and restricted cubic spline analysis were employed to assess the association between fibrinogen and CRC. When fibrinogen levels were divided into quartiles, the ORs for CRC in Q2, Q3, and Q4 compared to Q1 were 2.72 (95% CI: 1.57–4.74), 4.84 (95% CI: 2.84–8.25), and 9.55 (95% CI: 5.55–16.43), respectively. Restricted cubic spline analysis identified a non-linear association between fibrinogen levels and CRC risk with a threshold of 3.794 (95% CI: 3.747–3.841) g/L. Below this threshold, the CRC risk significantly increased (OR 5.944, 95% CI 4.084–8.65, P < 0.001). These findings may offer new insights for the diagnosis and management of CRC.